2021
DOI: 10.1016/j.jogoh.2021.102166
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the first lockdown for coronavirus 19 on breast cancer management in France: A multicentre survey

Abstract: Objective This study examined the impact of lockdown for SARS-CoV-2 on breast cancer management via an online survey in a French multicentre setting Material and methods This is a multicentre retrospective study, over the strict lockdown period from March 16 th to May 11 th , 2020 in metropolitan France. 20 centres were solicited, of which 12 responded to the survey Results 50% of the cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…Oncologic and diabetic patients included in a CP and also infected by SARS-CoV-2 were admitted to the COVID ward of the same hospital, ensuring a partial continuity of care, as well as already reported for oncological care in other experiences and where specific CPs for COVID-19 were ensured [ 5 , 32 ]. Whereas, regarding the continuity of care for patients affected by both DSA and SARS-CoV-2, the number of cases was small, and it was not necessary to create separate pathways and/or wards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oncologic and diabetic patients included in a CP and also infected by SARS-CoV-2 were admitted to the COVID ward of the same hospital, ensuring a partial continuity of care, as well as already reported for oncological care in other experiences and where specific CPs for COVID-19 were ensured [ 5 , 32 ]. Whereas, regarding the continuity of care for patients affected by both DSA and SARS-CoV-2, the number of cases was small, and it was not necessary to create separate pathways and/or wards.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to the multidisciplinary meetings for the discussion of cases using teleconferencing, this new system was used both by our respondents and in other settings [ 12 , 29 , 32 ]. Some studies report additional information, for example, the study by Fersia et al [ 29 ] was also focused on extra benefits ensured to patients’ care, as the teleconference systems allowed the involvement of other colleagues from different hospitals [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed and reported the extent to which consultation rates of patients and healthcare services have been impacted during the COVID-19 pandemic compared to pre-pandemic times. These have included patient delays in seeking medical care, declines in hospitalisations for acute medical conditions such as strokes and myocardial infarctions (with reductions ranging from 20.2 to 73.0%), impact on routine cancer care, less utilisation of in-hospital procedures such as coronary angiographies, postponing or cancellation of surgical procedures, and shorter length of hospital stays [ 9 , 10 , [18] , [19] , [20] ]. Several studies have also reported on the impact of the COVID-19 pandemic on primary care services.…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative interview study of GPs in the Flemish part of Belgium to gain insights into the consequences of the COVID-19 outbreak on the core functions of primary care, there was a major switch towards telephone triage and consult, there was a feeling that acute care was compromised, chronic care was mostly postponed and there was a worry about continuity of regular care [ 17 ]. Though there is some data on healthcare professional views on the impact of the COVID-19 pandemic on healthcare services such as cancer care management, arthroplasty services, and routine care for chronic diseases [ 11 , 15 , 18 , 19 ], there is limited data for primary care diabetes services specifically. Our study provides a previously unreported comprehensive assessment of the perspectives of healthcare professionals regarding the impact of the COVID-19 pandemic on the delivery of primary care for diabetes in UK primary care.…”
Section: Discussionmentioning
confidence: 99%
“…The containment measures of the COVID-19 pandemic in 2020 resulted in massive social changes worldwide. This was also the case in the health sector and, in particular, in cancer counseling [1][2][3][4][5][6][7]. The changes caused by the pandemic made it necessary to restructure counseling-specific concepts in order to ensure continuity of support.…”
Section: Introductionmentioning
confidence: 99%